THE PREDICTING FACTORS OF MUSEUM VISITOR INTENTION: A STUDY OF MUSEUM WAYANG JAKARTA - Ichwan Masnadi (Jurnal Hospitality dan Pariwisata, 2023)
Abstract       This study examines the influence between the product and the management of attraction on revisit intentions. The sample were taken by accidental sampling method of 150 respondents. Data were collected by survey with questioner method, field orientation, and interview. The data were analyzed using multivariate regression analysis to determine the influence between the product, the management of attraction and revisit intention. The product consist of location, accessibility, variety on site attractions, high quality environment, facilities, and price. The result showed that accessibility, variety on site attraction, and facilities has a significantly positive effect on revisit intention, meanwhile environment and price was not significantly influence on revisit intention. On the contrary, location has a negative effect on revisit intention. The management of attractions include the tangible elements of product, the characteristics of service delivery, and human resources management. The tangible elements of product and human resources was not significantly influence on revisit intention, but the characteristics of service delivery has a positive influence on revisit intention. The result indicate that the product has a dominant and significantly positive influence on revisit intention and the management of attractions also has a significantly positive effect on revisit intention . The product and management of attractions simultaneously has a significantly positive effect on revisit intention. The study provided a more through understanding the factors that may effect success of museum, which may help governments better understand the visitor needs.